Low reynolds number numerical simulation of the aerodynamic coefficients of a 3D wing - Malik, Khurshid; Asrar, Waqar; Sulaeman, Erwin (Embry Riddle Aeronautical University, 2018)
A low Reynolds number, three-dimensional CFD analysis is carried out for a finite flat plate wing using the commercial CFD code STAR CCM+. The six-aerodynamic force and moment components CL, CD, CM, CN, Cl, CY and their derivatives are computed at a Reynolds numbers of 3x105 by varying the pitch, roll and yaw angles about the quarter chord point. The computed results have been validated with experimental aerodynamic balance data when possible. The results indicate that roll and yaw angle affect the aerodynamic coefficients of the flat plate wing along with the pitch angle. The influence of roll and yaw angles on the six aerodynamics coefficients were found to be significant for high pitch angles specially 10 and 15. Stability derivatives have also been reported. This data is important for the design of MAVs and small UAVs and is currently perhaps not available in the open literature.